Plasma Beam Dumps for the EuPRAXIA Facility - Guoxing Xia; Alexandre Bonatto; Roger Pizzato Nunes; Linbo Liang; Oscar Jakobsson; Yuan Zhao; Barney Williamson; Can Davut; Xueying Wang (Instruments, 2020)
Beam dumps are indispensable components for particle accelerator facilities to absorb or dispose beam kinetic energy in a safe way. However, the design of beam dumps based on conventional technology, i.e., energy deposition via beam–dense matter interaction, makes the beam dump facility complicated and large in size, partly due to the high beam intensities and energies achieved. In addition, specific methods are needed to address the radioactive hazards that these high-power beams generate. On the other hand, the European Plasma Research Accelerator with eXcellence in Application (EuPRAXIA) project can advance the laser–plasma accelerator significantly by achieving a 1–5 GeV high-quality electron beam in a compact layout. Nevertheless, beam dumps based on the conventional technique will still produce radiation hazards and make the overall footprint less compact. Here, a plasma beam dump will be implemented to absorb the kinetic energy from the EuPRAXIA beam. In doing so, the overall compactness of the EuPRAXIA layout could be further improved, and the radioactivity generated by the facility can be mitigated. In this paper, results from particle-in-cell simulations are presented for plasma beam dumps based on EuPRAXIA beam parameters.